PENGGUNAAN DEIKSIS SEMANTIK DALAM CERPEN SILUET JINGGA KARYA ANGGI P - Rini Damayanti (Buana Bastra, 2015)
Abstract This research aims to determine the use of form semantic deixis that contained in Siluet Jingga short story by Anggi P. The method used in this research is a descriptive with qualitative study. Based on data analysys, it can be concluded that 1) deixis persona represented by I, we, our (as deixis first persona), you (as second deixis persona), he/she, and they (as third deixis persona) 2) deixis concerning personal name are Jingga, Nduk. 3) Deixis concerning the demonstrative pronouns this and that, and 4) Deixis concerning tim e in Siluet Jingga stories that day and a year ago. Key Words: deixis, semantic deixis.